SISTEM PENDUKUNG KEPUTUSAN UNTUK MENENTUKAN PEGAWAI TERBAIK MENGGUNAKAN METODE SUGENO DI KANTOR KECAMATAN SAGULUNG KOTA BATAM - Aranski, Alvendo Wahyu (JURNAL SITEBA, 2025)
In a performance appraisal process in an institution, employees are the first spearhead in the community service process. The performance of each employee will show the quality of employees in carrying out their duties. It aims to see the extent to which the performance of employees, improvement and supervision of performance for employees. So that institutional leaders can make decisions to choose the best employees from the best. The assessment includes service orientation, integrity, discipline, commitment and cooperation. So far, there is no system that can be used to determine the best employees. Therefore, this study uses a decision-making system using fuzzy logic with the zero-order Sugeno method to assess the performance of employees at the Sagulung District Office. Data processing using MATLAB. The first step in completing the employee performance appraisal using the Sugeno method is to determine the input variables and output variables which are firm sets, the second step is to change the input variables into fuzzy sets with a fuzzification process. The output variable is the decision of selecting the best employee with the Output (Best/Enough/Poor). The results obtained in this study used three data. The first and third employees with manual calculation of values ​​and calculations using MatLab Software Both manual calculations and using MatLab both show competent fuzzy output categories. So that Sugeno's fuzzy logic can be applied to determine the best employees in Sagulung District.